On estimating uniform distribution via linear Bayes method. Issue 19 (2nd October 2017) - Wang, Lichun; Wang, Haocheng
ABSTRACT: A linear Bayes procedure is suggested to simultaneously estimate the parameters of the uniform distribution U (θ1, θ2 ). The proposed linear Bayes estimator is simple and easy to use and its superiorities are established.